A scoping review on biomedical journal peer review guides for reviewers - Song, Eunhye; Ang, Lin; Park, Ji-Yeun; Jun, Eun-Young; Kim, Kyeong Han; Jun, Jihee; Park, Sunju; Lee, Myeong Soo (PLOS ONE, 2021)
Background Peer review is widely used in academic fields to assess a manuscript’s significance and to improve its quality for publication. This scoping review will assess existing peer review guidelines and/or checklists intended for reviewers of biomedical journals and provide an overview on the review guidelines. Methods PubMed, Embase, and Allied and Complementary Medicine (AMED) databases were searched for review guidelines from the date of inception until February 19, 2021. There was no date restriction nor article type restriction. In addition to the database search, websites of journal publishers and non-publishers were additionally hand-searched. Results Of 14,633 database publication records and 24 website records, 65 publications and 14 websites met inclusion criteria for the review (78 records in total). From the included records, a total of 1,811 checklist items were identified. The items related to Methods, Results, and Discussion were found to be the highly discussed in reviewer guidelines. Conclusion This review identified existing literature on peer review guidelines and provided an overview of the current state of peer review guides. Review guidelines were varying by journals and publishers. This calls for more research to determine the need to use uniform review standards for transparent and standardized peer review. Protocol registration The protocol for this study has been registered at Research Registry (www.researchregistry.com): reviewregistry881.